Pontin Acts as a Potential Biomarker for Poor Clinical Outcome and Promotes Tumor Invasion in Hilar Cholangiocarcinoma. (13th May 2018) - Sun, Qi; Li, Fanni; Yu, Songyang; Zhang, Xiang; Shi, Feiyu; She, Junjun
Abstract : Hilar cholangiocarcinoma (HC) is a devastating malignancy that carries a poor overall prognosis. As a member of the AAA+ superfamily, Pontin becomes highly expressed in several malignant tumors, which contributes to tumor progression and influences tumor prognosis. In our research, Pontin expression in tumor specimens resected from 86 HC patients was detected by immunohistochemistry. Interestingly, high expression of Pontin was significantly associated with lymph node metastasis (p = 0.011 ) and tumor node metastasis (TNM) stage (p = 0.005 ). The Kaplan–Meier overall survival rate and multivariate analyses were performed to evaluate the prognosis of patients with HC. Patients with high Pontin expression had significantly poorer overall survival outcomes. Multivariate analyses found that Pontin was an independent prognostic factor (p = 0.001 ). Moreover, bioinformatics analysis confirmed the increase in Pontin mRNA expression levels in cholangiocarcinoma tissues. In addition, in vitro experiments showed that Pontin expression was inhibited at the mRNA as well as protein levels after transfection with Pontin siRNA in human cholangiocarcinoma cell lines. Moreover, significant suppression of cell invasion was observed after the downregulation of Pontin. Taken together, the present study suggested that Pontin could act as a potential prognostic predictor, which might be a new valuable molecular candidate for the prevention and treatment of HC.